Novel Hujan Bulan Juni Karya Sapardi Djoko Damono dan Madrasah Cinta Karya Ayu Nesia (Kajian Intertekstual) - Anggraini, Tri Riya; Awalludin, Awalludin; Basuki, Basuki (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
The aim of this research is to identify the similarities and differences between the two in Sapardi Djoko Damono's novel "Rain Bulan Juni" and Ayu Nesia "Madrasah Cinta". This type of qualitative descriptive research. As intertextual support in the novel, this research data is information that is used as an object of study in every word and sentence expression. Madrasah Cinta by Ayu Neisa and June Rain by Sapardi Djoko Damono. This data was collected through the library method, which means the data was collected through literature. From the analysis data that has been found, it can be informed that the similarities in the novel Rain Bulan Juni and the novel Madrasah Cinta are related to the theme, namely that they are both related to how to live a life-love relationship. The plots both use a mixed plot and both use a third person point of view. Meanwhile, there are differences in background aspects, both in terms of place, time and atmosphere. Apart from that, the difference is related to the message contained in the novel June Rain, namely the existence of tolerance between religious communities. Meanwhile, the message contained in the love madrasa novel as conveyed by the author (Habiburrahman El Shirazy) is that our lives must be neatly arranged, planned... Marriage is the sunnah of the Prophet, don't delay when the time comes.